PERNIKAHAN DALAM PERSPEKTIF HUKUM ISLAM - Malik Adharsyah; Muhammad Sidqi; Muhammad Aulia Rizki (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2024)
Marriage in Islam is not merely a bond between two individuals; it is a concept that embraces religious, moral, and social values. As one of the pillars of Islam, marriage holds wisdom and broader objectives, teaching believers to appreciate Allah's wisdom in creating life partners who complement each other. From the perspective of Islamic law, marriage is implemented as the tradition of Prophet Muhammad, providing a moral and spiritual foundation for the Islamic community. The ijab-qabul process is a key element, with a deep understanding of the rights and responsibilities of both spouses.Islamic marriage involves the family, with the approval of a guardian indicating familial support. Islamic law details the rights and duties of spouses, establishing the foundation for a balanced relationship. It also serves to prevent adultery, safeguarding society from moral decay. While Islam values marriage, it also provides detailed procedures for divorce. This process is considered a last resort requiring careful consideration and fairness. Marriage in Islam extends beyond worldly life, aiming to bring individuals closer to Allah in the hereafter.The research methodology employs a normative approach, referencing Islamic legal literature. Fundamental concepts of marriage, the pillars of nikah, and the wisdom of marriage are the primary focus of the discussion. From the perspective of Islamic law, marriage creates a robust foundation for building relationships that are balanced, just, and blessed